REMOTE SENSING AND GIS APPROACHES TOWARD SUSTAINABLE MANAGEMENT OF MARINE AQUACULTURE IN INDONESIA - I Nyoman Radiarta (Indonesian Aquaculture Journal, 2013)
The sustainable marine aquaculture (mariculture) has become increasingly important with the dramatic growth of the sector. To ensure long-term sustainability, planning is an important process that will stimulate and guide the evaluation of the sector. Many of the mariculture issues are entirely spatial in nature (e.g. siting, zoning), or have important spatial elements (potential mariculture areas, impact of mariculture, competition for space with other users). Satellite remote sensing integrated with geographic information systems (GIS) can play a major role in all geographic and spatial aspects of the development and management of mariculture. The potential capabilities of evolving GIS and remote sensing for the sustainability of mariculture provide a powerful tool for the efficient and cost effective management. These technologies are also useful for facilitating the decision making process in relation to mariculture. In this paper attempt to simply describe a number of ways in which GIS and remote sensing could be usefully employed as an aid to support sustainable mariculture development.